PENGENALAN ANGKA DAN HITUNGAN DALAM BAHASA INGGRIS DENGAN METODE MONTESSORI PADA ANAK USIA DINI - Sari Harahap, Faradiba (COVIT (Community Service of Tambusai), 2022)
This community service activity is carried out to provide knowledge about an English language learning method about numbers and calculations, namely the Montessori method. The target of this community service activity is students at Harapan Bunda Early Childhood Education (PAUD) Tanjungbalai City. The purpose of this activity is to provide information and increase knowledge about a concrete number learning method in English using the Montessori method. The activity method used in this community service is the lecture method and direct practice. The results of this activity show that when exploring teaching materials children feel free and confident when given the opportunity to move with a purpose. It is clear that freedom of boundaries is needed so that students can more easily understand the concepts being taught through direct and concrete experiences that are received by their senses. It is hoped that this series of community service activities will make it easier for students to remember and understand basic counting concepts using English in a concrete way through the Montessori method. Keywords: Montessori Method, English Learning, Early Childhood